2012
DOI: 10.5588/ijtld.11.0457
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tobacco dependence in waterpipe smokers in Egypt

Abstract: Summary Setting Waterpipe smoking is increasing worldwide. Nevertheless, little is known about nicotine dependence in tobacco smokers who use waterpipes. Objective To assess evidence of dependence among non-cigarette smoking waterpipe smokers in Egypt. Methods A total of 154 male exclusive current waterpipe smokers were enrolled for the present study. We adapted the Fagerström test for nicotine dependence and the Reasons for Smoking (RFS) scales and related these to smoking behavior. Results The mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 30 publications
1
34
1
2
Order By: Relevance
“…This is particularly concerning for adolescents and young adults, given that early exposure to nicotine increases the severity of future nicotine dependence (32) and the prevalence of water pipe use among these age groups. Further, tobacco dependence has been observed among regular water pipe users in Egypt (33), and is a concern in occasional users.…”
Section: Nicotine Intakementioning
confidence: 99%
“…This is particularly concerning for adolescents and young adults, given that early exposure to nicotine increases the severity of future nicotine dependence (32) and the prevalence of water pipe use among these age groups. Further, tobacco dependence has been observed among regular water pipe users in Egypt (33), and is a concern in occasional users.…”
Section: Nicotine Intakementioning
confidence: 99%
“…We previously conducted a baseline smoking prevalence survey in nine villages in the Qalyubia governorate in Delta Egypt ( Auf et al, 2012 ;Boulos et al, 2009 ;Radwan et al, 2007 ). In each village, 300 households were selected using a systematic random sample, and adults (aged ≥ 18 years) were interviewed for their demographics, smoking and quitting behaviors, exposure to ETS, and their knowledge, attitudes , and practices toward a variety of smoking-related variables.…”
Section: Study P Articipantsmentioning
confidence: 99%
“…For example, Auf et al (2012) recently demonstrated that, according to a modified Fagerström Test for Nicotine Dependence (FTND) (Heatherton, Kozlowski, Frecker, & Fagerström, 1991), WTSonly men (mean age = 47 years) in Egypt exhibited many of the same features of nicotine dependence attributed to cigarette smokers. Researchers in Lebanon developed a scale specifically intended to measure addiction to WTS.…”
mentioning
confidence: 99%